Changes in Social Networks and Farmers' Consumption Patterns (Architecture Image Studies, 2026)
The COVID-19 pandemic has placed society on the edge of concern, including eucalyptus oil farmers in Buru Regency, Indonesia. This study seeks to explore pre-existing social networks and eating habits where the social structure of society is in a traditional position. The method used is qualitative with a phenomenological approach. Informants in this study were identified through purposive techniques that involve researchers in making deliberate choices based on predetermined criteria and determining them according to the study's objectives. Data was collected using interview techniques, and the implementation time was day and night so as not to interfere with the informant's working time. The informants in this study were 20 eucalyptus oil farmers, 10 eucalyptus tree land owners, and 10 eucalyptus oil collectors. Data analysis was conducted using a thematic pattern in four stages: the collection of categories, direct interpretation, the formation of patterns, the search for equivalence between two or more categories, and the development of naturalistic generalizations by researchers. The study results show that the pandemic has changed the long-established social network into a rational relationship; limited livelihoods have caused farmers to abandon subsistence and use rational rhythms. The consequences of rational relationships give rise to suspicion, instability, and mutual suspicion, which opens up opportunities for conflict. The social structure formed by emotional relationships tends to weaken when the pandemic becomes a social fact that forces the emergence of conformity from eucalyptus oil farmers. Another result of this study is a change in eating habits prioritizing "adaptation and availability" rather than old habits based on local culture. The rational choices made by eucalyptus oil farmers in fulfilling consumption have resulted in a shift from traditional to rational.